Performance of the State Civil Apparatus (ASN) at the Mount Merbabu National Park Office - Laksana, Angki Hendrawan; Mursito, Bambang; Sakidi, Sakidi (UPN Veteran Yogyakarta, 2023)
This study investigates the impact of education level, loyalty, work facilities, and information technology applications on the performance of State Civil Apparatus (ASN) at the Gunung Merbabu National Park Office. The study uses a mixed-method approach, including observation, documentation, interviews, questionnaires, and literature studies. The population consists of 54 employees, with a sample size of 54 using saturated sampling. Data analysis is conducted using multiple linear regression. The findings reveal that education level and loyalty have a positive and significant effect on the performance of ASN at the Gunung Merbabu National Park Office. Work facilities also have a positive and significant influence on performance, while information technology has a positive but insignificant effect. These results suggest that enhancing education levels, fostering loyalty, and improving work facilities can improve the performance of ASN at the Gunung Merbabu National Park Office.